Enhancing executive mathematics problem-solving through a constructivist digital learning platform: Design, development and evaluation - Supaluk Chaiarwut; Sanit Srikoon; Apirat Siritaratiwat; Parama Kwangmuang (Social Sciences and Humanities Open)
Recent international assessments have highlighted a global decline in mathematics performance, particularly among students in Thailand. This study aims to (1) design and evaluate a constructivist learning innovation model on a digital platform that promotes executive mathematics problem-solving and (2) develop and assess a prototype based on the designed model. A mixed-method research design was employed across two phases. Phase 1 involved designing and evaluating the learning model through document analysis and expert validation (n = 9). Phase 2 focused on developing and testing a prototype with experts (n = 15) and students (n = 30). Data collection utilized the Index of Item-Objective Congruence (IOC), System Usability Scale (SUS), and User Engagement Scale (UES). The model showed strong alignment with theoretical principles (IOC = 0.84). The prototype showed excellent usability (SUS = 91.0/100) and high engagement (UES = 4.26/5.00). Expert evaluations indicated high quality in content (M = 4.47, SD = 0.48), media (M = 4.40, SD = 0.50), and innovation design (M = 4.59, SD = 0.64). The findings validate the model's efficacy in promoting executive mathematics problem-solving skills through a constructivist digital platform approach.